Rural E-Commerce and Income Growth: Exploring the Nexus of Digital Entrepreneurship in Rural Economies - Sonawane, Ujwala; Todiwan, Laxmi (Journal of Global Economy, Business and Finance, 2026)
This paper explores the relationship between rural e-commerce, rural entrepreneurship, and rural income under the backdrop of "Internet + entrepreneurship" based on panel data from the rural statistical yearbooks of 29 provinces and municipalities in China from 2013 to 2019. The study finds that the development of rural e-commerce and farmers' entrepreneurship are positively correlated with farmers' income. Notably, the impact of fiscal support for agriculture on farmers' income is not significant, while the level of education has a noticeable effect on farmers' income. These results remain valid in robustness tests. Based on the above analysis, this article puts forward recommendations for the development of rural e-commerce and boost farmers’ income under the context of "Internet + entrepreneurship." This article enriches the research related to how rural e-commerce enhances the well-being of farmers, and provides a theoretical basis and empirical reference for how to promote entrepreneurship and income generation through e-commerce models in the digital economy era.